Certain aspects of biology of the freshwater crab Travancoriana schirnerae (Bott, 1969) (Brachyura: Gecarcinucidae) - Sudha Devi, A. R.; Smija, M. K. (Indian Journal of Fisheries, 2014)
Biology of the freshwater crab Travancoriana schirnerae was studied with respect to sexual dimorphism and sex ratio from June 2009-August 2011. A total of 3605 individuals were collected of which 2168 (60.3%) were males and 1437 (39.7%) females. The sampled population comprised of juvenile males (15.3%), adult males (45%), juvenile females (9.3%), adult non-ovigerous (27.9%), ovigerous (0.6%) and juvenile bearing females (1.9%) and grouped into six size classes (0-1, 1.1-2, 2.1-3, 3.1-4, 4.1-5 and 5.1-6 cm). Results of this study indicated that the population exhibited sexual dimorphism with reference to size, chelae and cheliped dimensions and abdomen morphology. Adult males were heterochelous whereas females exhibited both heterochely and isochely in almost equal proportion (53 and 47% respectively). No significant difference was found in handedness preponderance for the sexes. Chi-square analysis showed that the sex ratio of the population significantly deviated from the 1:1 ratio with males outnumbering females.